2020
DOI: 10.2298/tsci180608062k
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of solar assisted multigenerational system using therminol VP1 based nanofluids: A comparative study

Abstract: The application of the nanofluids is suggested to enhance and improve the efficiency of solar thermal power system. In the present study, three different nanofluids (Fe2O3/therminol VP1, SiO2/therminol VP1, and Cu/therminol VP1) are numerically investigated in parabolic dish solar collector that is further integrated to a combined cycle for power and hydrogen production. Heat rejects from the power cycle is also utilized to drive a single effect absorption (LiBr-water) system. Furthermore, a comprehensive ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Many researchers have studied the use of nanofluid as a working fluid in solar cooling systems and several studies [31], [32] show that nanofluid can improve the efficiency of solar collectors. Salem et al [33] and Ande et al [34] studied the behavior of an air conditioning chiller working with water-Al2O3 nanofluid and they observed that less time was taken to obtain desired cooling temperature and also that there was a significant improvement in COP. Colangelo et al [36] and Milanese et al [37], [38] studied the use of nanofluid in solar thermal collectors.…”
Section: Nanofluids As Heat Transfer Fluids In Heating/cooling Systemmentioning
confidence: 99%
“…Many researchers have studied the use of nanofluid as a working fluid in solar cooling systems and several studies [31], [32] show that nanofluid can improve the efficiency of solar collectors. Salem et al [33] and Ande et al [34] studied the behavior of an air conditioning chiller working with water-Al2O3 nanofluid and they observed that less time was taken to obtain desired cooling temperature and also that there was a significant improvement in COP. Colangelo et al [36] and Milanese et al [37], [38] studied the use of nanofluid in solar thermal collectors.…”
Section: Nanofluids As Heat Transfer Fluids In Heating/cooling Systemmentioning
confidence: 99%
“…Density of hybrid nanofluids is an important parameter that influences the friction factor, pressure drop and Reynolds number of the fluid and it has inverse relation to the volumetric concentration. 60 The specific heat capacity of nanofluids is given by:…”
Section: Heat Transfer Analysismentioning
confidence: 99%
“…The volume fraction rising led to a reduction in the optimal Reynolds number. Khan et al [17] studied the effect of applying nanofluids in a solar-based cycle from an energy, exergy, and exergo-environmental point of view. The influence of three nanofluids, including Fe2O3/Therminol VP1, SiO2/Therminol VP1, and Cu/Therminol VP1, were compared by considering different parameters.…”
Section: Introductionmentioning
confidence: 99%